2010
DOI: 10.1177/1352458510361357
|View full text |Cite
|
Sign up to set email alerts
|

Predicting habitual walking performance in multiple sclerosis: relevance of capacity and self-report measures

Abstract: The objective was to establish the extent to which physical functioning capacity and self-report measures are able to predict the habitual walking performance in ambulatory persons with multiple sclerosis. Fifty persons with multiple sclerosis (Expanded Disability Status Scale, EDSS, 1.5-6.5) were tested on leg muscle strength as well as walking and balance capacity, and completed self-report indices on perceived physical functioning. Habitual walking performance, that is, the real amount of steps that is perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
118
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(126 citation statements)
references
References 47 publications
4
118
4
Order By: Relevance
“…Until further research is carried out on the psychometric properties of these measures using larger sample sizes in When 6MW data for this study were split into group A and group B, the SEM values for those with less disability decreased and the SEM values for those with greater disability increased. Interestingly, the mean distance walked by our minimally disabled group was 353.36 m, which is more similar to the result for the severely disabled group (EDSS 4.5-6.5) in the study by Goldman et al 10 Our more disabled group had a slower speed, averaging 228.15 m in 6 minutes, similar to the moderate MS group in the study by Gijbels et al, 9 who achieved a mean distance of 294 m, and to those with EDSS scores of 5 to 6.5 in the study by Learmonth et al,27 who scored 246.88 m. The method of stratifying to disability (GNDS vs. EDSS) may explain this difference in walking speed in our minimally disabled group.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Until further research is carried out on the psychometric properties of these measures using larger sample sizes in When 6MW data for this study were split into group A and group B, the SEM values for those with less disability decreased and the SEM values for those with greater disability increased. Interestingly, the mean distance walked by our minimally disabled group was 353.36 m, which is more similar to the result for the severely disabled group (EDSS 4.5-6.5) in the study by Goldman et al 10 Our more disabled group had a slower speed, averaging 228.15 m in 6 minutes, similar to the moderate MS group in the study by Gijbels et al, 9 who achieved a mean distance of 294 m, and to those with EDSS scores of 5 to 6.5 in the study by Learmonth et al,27 who scored 246.88 m. The method of stratifying to disability (GNDS vs. EDSS) may explain this difference in walking speed in our minimally disabled group.…”
Section: Discussionsupporting
confidence: 75%
“…The 6-Minute Walk test (6MW) is a simple functional walking test that measures exercise capacity and endurance levels and is a good predictor of habitual walking. 9 Goldman et al 10 found a strong relationship between the 6MW and subjective measures of ambulation and physical fatigue in 40 people with MS. They stratified their population by Expanded Disability Status Scale (EDSS) score and found mean distances of 603 m, 507 m, and 389 m for those with mild, moderate, and severe disability, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Studies use conventional gait parameters to assess the association between depressive symptoms and gait dysfunction [19]. Accelerometers are increasingly used to assess physical activity in pwMS [20]. Assessment of habitual walking behavior by means of accelerometers might also have the potential to investigate the effectiveness of pharmacological interventions [21].…”
Section: Discussionmentioning
confidence: 99%
“…In subjects with lower limb amputations, the distance walked is well correlated with daily activity and indicative for substantial functional limitations in daily life [33,34].Timed walk tests have not yet been validated specifically for users of KAFOs, but for patients with neurologic conditions that may require fitting of a KAFO such as incomplete SCI, stroke, traumatic brain injury, or multiple sclerosis [35][36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%